Testing Linear and Log-Linear Regressions with Autocorrelated Errors - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1984)
This paper considers the problem of testing linear and log-linear models with autocorrelated errors. Test of functional form as well as functional form and autocorrelation simultaneously are obtained using the Lagrange multiplier approach.